Acculturation in Javanese Traditional Medicine Practice in Yogyakarta - Triratnawati, ATIK (Komunitas, 2016)
The rampant practice of traditional medicine in the big cities in Java can not be separated from the influence of globalization. The practice of traditional medicine advertised through flyers, pamphlets, signage, television and internet. In medical practice, it can not be separated from the mixture of elements of the local culture, external/ foreign as well as modern medical later adopted in order to enhance public interest in their treatment. The purpose of this article is to analyze the practice of acculturation in traditional medicine both related to methods, tools, how to advertise and meaning behind the ways the adoption of other culture into the traditional practice.An intergrative ethnographic study was conducted in Bantul and Sleman, Yogyakarta, on traditional healers such as gurah, bekham, metaphysical/ spiritual, herbal, traditional massage therapy, as well as traditional healers specifically hemorrhoids. Other information was obtained from interviews with their patients.Medical pluralism by wrapping traditional therapy combined with health culture from the outside to attract consumers with a dogmatic way in order to improve the clients made by Javanese traditional healers. They advertise with testimony on local television screen with the aim of introducing methods, tools, disease cure rates, fees, in order made populair so the number of patients increases. Acculturation appears that more and more people believe in business practices and its treatment.